-6(5+6x)=-6x

Simple and best practice solution for -6(5+6x)=-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(5+6x)=-6x equation:



-6(5+6x)=-6x
We move all terms to the left:
-6(5+6x)-(-6x)=0
We add all the numbers together, and all the variables
-6(6x+5)-(-6x)=0
We multiply parentheses
-36x-(-6x)-30=0
We get rid of parentheses
-36x+6x-30=0
We add all the numbers together, and all the variables
-30x-30=0
We move all terms containing x to the left, all other terms to the right
-30x=30
x=30/-30
x=-1

See similar equations:

| 10+4=6y | | f−98=95​ | | 5(n+11)=85 | | 10t-4=5t+1 | | 3+4z=11 | | 7a=a+6 | | 6k+31=-6k-6(-2k-6) | | 5y+35=5 | | 5b-3=2b | | -25y+13=38 | | E^(3x)-6=150 | | -3x+53+11x+21=90 | | 10(g-86)=8 | | 6y=30-12 | | 2t-5=t-2 | | b^2+28b-27=23 | | -8y-20=4 | | 16x-16=90 | | y=-2(1)^2-4(1) | | 2b+1=3b | | y=-2(1)^2-4(1 | | 2(x+7)-7=7 | | 16x-16+4x+26=90 | | 1=x-x^2 | | q^2-2q=15 | | 20y-30=20 | | 7w-6=4 | | 6y+9=15 | | 4=s+2 | | 10=2p/12 | | (14x-22)+(5+55)=90 | | 3x-7=16-2x |

Equations solver categories